Efektivitas Kebijakan Pengelolaan Sampah Berbasis Tempat Pengelolaan Sampah Terpadu 3R di Indonesia - Fallita Rahma Wati; Alfin Rizqi; M. Iqbal M. Iqbal; Sabriani Sangga Langi; Dila Noviza Putri (PERSPEKTIF, 2021)
This study aims to identify and analyze the effectiveness of waste management policies based on the 3R Integrated Waste Management Site (TPST) in Indonesia and as a basis for consideration and evaluation for the central and local governments in making waste management policies. This is because waste management both at national and regional scales has not yet found the right solution, coupled with a growing population, so it is important to find appropriate waste management. This research method uses a qualitative approach by conducting literature studies from various relevant sources. The results of this study indicate that the TPST 3R-based waste management policy has not been optimal in its implementation. The effectiveness of the waste management policy is measured through Campbell's theory with several indicators, namely program success, target success, program satisfaction, suitability of input and output, and achievement of overall goals.